Knowledge Management Practices in Sport Institutions - اليوسف مضر (Latakia University Journal -Medical Sciences Series, 2024)
Knowledge management is concerned with identifying and utilizing valuable information and understanding knowledge assets. This paper aims to focus on the importance of Knowledge Management in the field of successful and distinguished management of sports institutions, through analyzing a number of recent Arab and Foreign Studies in this field, especially with regard to exploring the elements of knowledge management and its various processes in the development of the basic functions of sports management. It is necessary to study the extent to which various knowledge management practices affect the ways in which the Departments of sports institutions deal with the development of their managerial performance. Previous Arab Studies in the field of sports have shown that little attention has been paid to the knowledge management process in the field of sports education in general, while foreign studies have shown that the application of Knowledge Management in sports institutions is the main factor for success in reaching the realization of the concept of the knowledge economy and thus reaching a distinct and successful management of those institutions, by considering knowledge management as a continuous process and that the application of its four main processes (knowledge diagnosis, creation and generation of knowledge, dissemination of knowledge, storage of knowledge, application of knowledge) will contribute to the development of administrative functions represented in the processes of Planning, Organization, guidance and control.